Implementation Curriculum Islamic Studies in Shaping Spiritual Attitudes Scopus Data Analysis in Bibliometrics - Muhammad-Lawal, Adam Adesina; Firda Arvita, Rizky; Inayati, Nurul Latifatul; Apriyantoro, Muhammad Subhi (Journal of Educational Management and Strategy, 2025)
he purpose of this study is to map the development and direction of Islamic Studies Curriculum research published in Scopus-indexed journals between 1980 and 2023. A bibliometric research design was applied, utilizing data extracted from the Scopus database. The analysis was conducted using Excel and R/R-Studio, while VOSviewer was employed to visualize keyword co-occurrence networks and citation relationships. The findings reveal a total of 595 relevant publications that met the established criteria. The annual growth rate of research output was 9.26%, with 2022 identified as the peak year for publications. Indonesia was the country contributing the largest number of studies, with strong affiliations from institutions such as Riphah International University. In terms of authorship, Arvisais, O. emerged as the most prolific author within this research domain. Furthermore, the bibliometric mapping highlighted dominant thematic clusters including curriculum design, Islamic education, learning outcomes, and religious values. The implications of this study suggest that research on the Islamic Studies Curriculum is gaining increasing attention globally, particularly in Southeast Asia, and that there are significant opportunities for collaboration and innovation in this field. Future studies are recommended to expand the scope of analysis by including additional national and international databases beyond Scopus to capture a more comprehensive understanding of the research landscape.